Persepsi Siswa Kelas 5 terhadap Sikap Profesional Guru di SDN 11 Langkai - Noor Laila; Marsha Yustania; Ahmad Apandi; Syahwandi Syahwandi; Robi Robi; Tedi Sujarwono (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
The professional attitude possessed by a teacher is one of the main determinants that greatly influences the success of the implementation of education, especially at the Elementary School level which serves as the initial foundation for character formation, mastery of knowledge, and development of various skills possessed by students. This study aims to describe and understand in depth the views of students towards the professional attitudes shown by teachers, which are seen and reviewed from four main aspects, namely the ability to carry out the learning process, attitudes and behaviors shown, relationships established with students, and a sense of responsibility in carrying out all the tasks and obligations they carry. This study uses a qualitative approach with a descriptive type. The research subjects numbered 12 students who were selected intentionally and adjusted to the research objectives, all of whom came from grade 5 at SDN 11 Langkai, Palangkaraya City. Data collection was conducted through three main methods, namely in-depth and targeted interviews, direct observations, and a review of various supporting documents deemed relevant, which were carried out from April to May 2026. All data that had been successfully collected were then analyzed through three stages, namely data simplification, data presentation, and drawing conclusions, as stated by Miles, Huberman, and Saldana. To ensure the accuracy and reliability of the data obtained, the researcher implemented a method of checking the validity of the data through a comparison of various sources of information and different data collection methods. The results of the study showed that overall the views of 5th grade students towards the professional attitudes shown by the teachers were very positive. Most students assessed that the teachers were able to convey lesson materials very clearly, orderly, and easily understood, always behaved politely, honestly, and acted fairly without discriminating in the treatment of all students, were able to establish very close and trusting relationships, and had a very high level of sincerity and responsibility in carrying out all their duties. However, there are still some points that require attention, namely the speed of material delivery, which sometimes felt too fast, resulting in some students requiring additional explanations to fully understand the material. The results of this study are expected to serve as valuable input for teachers and school administrators as they strive to continuously improve the quality of their educational services.